Identification of Circular RNA Expression Profiles in White Adipocytes and Their Roles in Adipogenesis - Zhang, Peng-peng; Han, Qiu; Sheng, Ming-xuan; Du, Chun-yu; Wang, Ya-ling; Cheng, Xiao-fang; Xu, Hai-xia; Li, Cen-cen; Xu, Yong-jie (Frontiers in Physiology, 2021)
Obesity and its related metabolic diseases have become great public health threats worldwide. Although accumulated evidence suggests that circRNA is a new type of non-coding RNAs regulating various physiological and pathological processes, the functions of circRNAs in white adipose tissue remain largely unknown. In this study, 3,771 circRNAs were detected in three stages of white adipogenesis (preadipocyte, differentiating preadipocyte, and mature adipocyte) by RNA-seq. A total of 176 differential circRNAs expressions were detected between different adipogenesis stages. Experimental validation suggested the RNA-seq results are highly reliable. We found that nearly 10% of genes which expressed linear RNAs in adipocytes could also generate circRNAs. In addition, 40% of them produced multiple circRNA isoforms. We performed correlation analysis and found that as many as 50% of circRNAs and their parental genes are highly correlated in expression levels. KEGG and GO enrichment of the parental genes suggesting that circRNAs participate in a lot of metabolism terms and fat-related pathways. Notably, numerous histone modification GO terms were enriched, indicating the potential role of circRNAs in epigenetics. Following rigorous selection, we identified the up-regulated circRNAs during adipogenesis contain multiple binding sites for functional miRNAs, such as miR17, miR-30c, miR27a, and miR-13, indicating they may facilitate regulatory functions by acting as microRNA sponges. These identified circRNAs may serve as new candidates for future adipogenesis regulation.